Synthesis and Biological Evaluation of the Matrine Derivatives as a Novel Family of Potential Anticancer Agents - Wang, Jing; Liu, Hang; Zhuo, Xiao-Bin; Ye, Guang-Ming; Zhao, Qing-Jie (Medicinal Chemistry, 2021)
Background: FufangKushen injection’ was a Chinese Traditional anticancer drug, which has been widely used to treat cancer in combination with other anticancer drugs. Objective: Our goal is to synthesize a series of novel 13-dithiocarbamates matrine derivatives using matrine (1) as the lead compound, and evaluate the biological activities of the obtained compounds. Methods: The in vitro cytotoxicity of the target compounds against three human cancer cell lines (Hep3B, LM3 and BeL-7404) was evaluated. To investigate the mechanism of biological activity, cell cycle analysis was performed. Results: The results revealed that compounds 6o and 6v displayed the most significant anticancer activity against three cancer cell lines with IC50 values in the range of 3.42-8.05 μM, which showed better activity than the parent compound (Matrine). SAR analysis indicated that the introduction of a substituted amino dithiocarbamate might significantly enhance the antiproliferative activity. Conclusion: During the newly synthesized compounds, matrine analog 6v exhibited a potent effect against three human tumor cell lines. The mode of action of 6v was to inhibit the G0/G1 phase arrest. Therefore, compound 6v has been selected as a novel-scaffold lead to further structural optimizations or as a chemical probe for exploring anticancer pathways of this kind of compounds.
Keywords: cell cycle